Optimizing nitrogen rates for winter wheat using in-season crop N status indicators - Raffaele Meloni; Eleonora Cordero; Luca Capo; Amedeo Reyneri; Dario Sacco; Massimo Blandino (Field Crops Research, 2024)

The role of zinc fertilization and its interaction with nitrogen and phosphorus starter fertilization on early maize development and grain yield - Luca Capo; Michela Battisti; Massimo Blandino (Field Crops Research, 2024)

Mycotoxin occurrence in kernels and straws of wheat, barley, and tritordeum - Marco Gozzi; Massimo Blandino; Renato Bruni; Luca Capo; Laura Righetti; Chiara Dall’Asta (Mycotoxin Research, 2024)
Thirty-two varieties of common and durum wheat, hordeum, barley, and tritordeum collected over two harvesting years (2020 and 2021) were investigated for the presence of multiple Fusarium -related mycotoxins in asymptomatic plants. DON, 3-AcDON, 15-AcDON, T-2, HT-2, and ZEN together with the emerging mycotoxin ENN B and the major modified form of DON, namely DON3Glc, were quantified by means of UHPLC-MS/MS. Overall, DON and ENN B were the most frequently detected mycotoxins, albeit large inter-year variability was observed and related to different climate and weather conditions. Straws had higher mycotoxin contents than kernels and regarding DON occurrence tritordeum was found to be the most contaminated group on average for both harvesting years, while barley was the less contaminated one. Emerging mycotoxin ENN B showed comparable contents in kernels compared to straw, with a ratio close to 1 for tritordeum and barley. Regarding the occurrence of the other evaluated mycotoxins, T-2 and HT-2 toxins have been spotted in a few tritordeum samples, while ZEN has been frequently found only in straw from the harvesting year 2020. The data collected confirms the occurrence of multiple Fusarium mycotoxins in straws also from asymptomatic plants, highlighting concerns related to feed safety and animal health. The susceptibility of Tritordeum, hereby reported for the first time, suggests that careful measures in terms of monitoring, breeding, and cultural choices should be applied when dealing with his emerging crop.

Native mycorrhizal communities in maize roots as affected by plant genotype, starter fertilization and a seed-applied biostimulant - Gergely Ujvári; Arianna Grassi; Caterina Cristani; Irene Pagliarani; Luciano Avio; Massimo Blandino; Luca Capo; Manuela Giovannetti; Alessandra Turrini; Monica Agnolucci (Plant and Soil, 2023)
Background and aims One of the most promising strategies for sustainable intensification of crop production involves the utilization of beneficial root-associated microorganisms, such as plant growth-promoting bacteria and arbuscular mycorrhizal fungi (AMF). The aim of this study was to investigate whether a seed-applied biostimulant, based on the bacterial strain Bacillus amyloliquefaciens IT-45 and a plant polysaccharide extract, and crop enhancement tools, such as hybrids with contrasting early vigor and nitrogen (N) plus phosphorus (P) starter fertilization, and their interactions, shape the communities of native root-colonizing AMF symbionts in maize. Methods A factorial growth chamber experiment was set up with two maize genotypes in natural soil. Mycorrhizal colonization was evaluated after root staining. The diversity and composition of AMF communities were assessed by PCR-DGGE of the 18S rRNA gene and amplicon sequencing. Results N and P fertilization determined a consistent reduction of AMF root colonization and, in combination of biostimulant, a reduction of AMF richness. The biostimulant alone generally did not affect AMF colonization or the community biodiversity. In addition the effect of the two factors were modulated by maize genotype. In all treatments, predominant AMF were represented by Glomus sp. and Funneliformis mosseae , while populations of the genus Rhizoglomus were rarely detected in biostimulant and NP fertilization treatments. Conclusion The results of this study increase our understanding of how the biostimulant seed treatment may affect native AMF communities, depending on NP fertilization and maize genotype and may improve the implementation of innovative tools in sustainable and resilient agroecosystems.